Identifying the prevalence of aggressive behaviour reported by Registered Intellectual Disability Nurses in residential intellectual disability services: an Irish perspective. Issue 3 (29th April 2014) - Crotty, G.; Doody, O.; Lyons, R.
Abstract : Purpose: – Despite the high incidence of aggressive behaviours among some individuals with intellectual disability, Ireland has paid little attention to the prevalence of aggressive behaviours experienced by Registered Intellectual Disability Nurses (RNID). Within services the focus is mainly on intervention and management of such behaviours. Therefore a disparity occurs in that these interventions and management strategies have become the exclusive concern. Resulting in aggressive behaviour being seen as a sole entity, where similar interventions and management strategies are used for ambiguously contrasting aggressive behaviours. Consequently the ability to document and assess-specific behaviour typologies and their prevalence is fundamental not only to understand these behaviour types but also to orient and educate RNIDs in specific behaviour programme development. The paper aims to discuss these issues. Design/methodology/approach: – This study reports on a survey of the prevalence of verbal aggression, aggression against property and aggression against others experienced by RNIDs' within four residential settings across two health service executive regions in Ireland. A purposeful non-random convenience sampling method was employed. Totally, 119 RNIDs responded to the survey which was an adaptation of Crocker et al. (2006) survey instrument Modified Overt Aggression Scale. Findings: – The findings of this study showed the experienced prevalence rate of verbal aggression, aggression against property and aggression against others were 64, 48.9 and 50.7 per cent, respectively. Cross-tabulation of specific correlates identifies those with a mild and intellectual disability as displaying a greater prevalence of verbal aggression and aggression against property. While those with a moderate intellectual disability displayed a higher prevalence of aggression against others. Males were reported as more aggressive across all three typologies studied and those aged between 20 and 39 recorded the highest prevalence of aggression across all three typologies. The practice classification areas of challenging behaviour and low support reported the highest prevalence of aggression within all typologies. Originality/value: – The health care of the person with intellectual disability and aggressive behaviour presents an enormous challenge for services. In-order to improve considerably the quality of life for clients, services need to take a careful considered pragmatic view of the issues for the person with intellectual disability and aggressive behaviour and develop realistic, proactive and responsive strategies. To do this, precise knowledge of the prevalence of aggressive behaviours needs to be obtained. This study is the first of its kind in the Republic of Ireland.